2021
DOI: 10.1038/s41388-021-01781-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting vulnerabilities of SWI/SNF chromatin remodelling complexes for cancer therapy

Abstract: Multi-subunit ATPase-dependent chromatin remodelling complexes SWI/SNF (switch/sucrose non-fermentable) are fundamental epigenetic regulators of gene transcription. Functional genomic studies revealed a remarkable mutation prevalence of SWI/SNF-encoding genes in 20–25% of all human cancers, frequently driving oncogenic programmes. Some SWI/SNF-mutant cancers are hypersensitive to perturbations in other SWI/SNF subunits, regulatory proteins and distinct biological pathways, often resulting in sustained anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 144 publications
(237 reference statements)
0
71
0
4
Order By: Relevance
“…Immune checkpoint inhibitors, EZH2 antagonists, poly(ADP‐ribose) polymerase inhibitors and various other targeted therapies or specific chemotherapy regimens have been proposed for use in SWI/SNF complex‐deficient cases 45–48 . For example, EZH2 antagonists have been proposed as a rational therapeutic choice in SMARCA4‐deficient brain or ovarian tumours 46,47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoint inhibitors, EZH2 antagonists, poly(ADP‐ribose) polymerase inhibitors and various other targeted therapies or specific chemotherapy regimens have been proposed for use in SWI/SNF complex‐deficient cases 45–48 . For example, EZH2 antagonists have been proposed as a rational therapeutic choice in SMARCA4‐deficient brain or ovarian tumours 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Immune checkpoint inhibitors, EZH2 antagonists, poly (ADP-ribose) polymerase inhibitors and various other targeted therapies or specific chemotherapy regimens have been proposed for use in SWI/SNF complex-deficient cases. [45][46][47][48] For example, EZH2 antagonists have been proposed as a rational therapeutic choice in SMARCA4deficient brain or ovarian tumours. 46,47 This approach should currently be considered to be experimental, and if novel therapies for SWI/SNF complex-deficient tumours are validated it will become a challenge to identify them in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A and ARID1B co-inactivation appears to be an alternate mechanism to BRG1 or INI1, which results in the occurrence of the undifferentiated component [ 23 ]. Overall, ARID1A is the most frequently mutated SWI/SNF subunit across cancer types [ 29 ] and has a tumor-suppressive function, whereby it triggers cancer development by interfering with the DNA-damage response and cell cycle pathways [ 32 , 33 ]. Furthermore, several studies have also demonstrated that an ARID1A loss is associated with the activation of phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) and the concurrent loss of PTEN expression, which both activate the PI3K/AKT/ mTOR cell cycle pathway [ 34 , 35 , 36 , 37 ].…”
Section: Histological Diagnosis Immunohistochemistry and Genetic Alte...mentioning
confidence: 99%
“…Proteolysis-targeting chimeras induce ubiquitin transfer onto target proteins, thereby marking them for proteasomal degradation. This was applied to target BRD9, a SWI/SNF complex subunit [ 33 ]. For example, AU-15330 induced a potent inhibitor of tumor growth in xenograft models of prostate cancer, and synergized with the androgen receptor antagonist enzalutamide, even inducing disease remission in castration-resistant prostate cancer models without toxicity [ 60 ].…”
Section: Preclinical Data and Relevant Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation